Mid-term results of surgical aortic valve replacement with bioprostheses in hemodialysis patients. (June 2022) - Shibasaki, Ikuko; Fukuda, Taira; Ogawa, Hironaga; Tsuchiya, Go; Takei, Yusuke; Seki, Masahiro; Kato, Takashi; Kanazawa, Yuta; Saito, Shunsuke; Kuwata, Toshiyuki; Yamada, Yasuyuki; Haruyama, Yasuo; et al.
Highlights: HD patients underwent SAVR-BP for AS (hospital mortality, 8.8%; 5-year mortality, 42.1%). Preoperative risk factors for 5-year mortality: age, hyperlipidemia, LVDd, LVDs, and Japan SCORE. Postoperative risk factors for 5-year mortality: length of ICU stay, and albumin level at discharge. Abstract: Background: Limited studies have assessed the factors affecting prognosis in hemodialysis (HD) patients who undergo surgical aortic valve replacement with a bioprostheses (SAVR-BP). This study aimed to evaluate the outcomes of HD patients who had undergone SAVR-BP for aortic stenosis (AS) and identify the risk factors for mortality. Methods: This retrospective study included 57 HD patients who had undergone SAVR-BP for AS between July 2009 and December 2020. Multivariate logistic regression was used to predict factors associated with mid-term outcomes and death or survival. Kaplan − Meier curves were also generated for mid-term survival. Results: The in-hospital mortality rate was 8.8%, and the 5-year mortality rate was 42.1%. The independent predictors of 5-year mortality were preoperative age (hazard ratio [HR], 1.57; 95% confidence interval [CI], 1.175–2.083, p = 0.002), hyperlipidemia (HR, 0.02; 95% CI, 0.002–0.297, p = 0.004), left ventricular diastolic diameter (HR, 1.74; 95% CI, 1.142–2.649, p = 0.010), left ventricular systolic diameter (HR, 0.61; 95% CI, 0.392–0.939, p = 0.025), and Japan SCORE (HR, 1.28; 95% CI, 1.052–1.563, p = 0.014). The postoperative predictors included intensive care unit stay (HR, 1.11; 95% CI, 1.035–1.194, p = 0.004) and albumin level (HR, 0.38; 95% CI, 0.196–0.725, p = 0.003). Conclusions: The 5-year prognosis of HD patients undergoing SAVR may be improved by early diagnosis (before the occurrence of LV hypertrophy/enlargement) and nutritional management with oral intake to alleviate postoperative hypoalbuminemia. Registration number of clinical studies: UMIN000047410.